0089 Does Good Sleep Efficiency Protect Against the Cognitive Consequences of Anxiety Symptoms in Older Adults?. (27th April 2018) - Perez, E; Dzierzewski, J M; Aiken-Morgan, A T; McCrae, C S; Buman, M P; Giacobbi, P R; Roberts, B L; Marsiske, M
Abstract: Introduction: Anxiety symptoms and poor sleep are highly prevalent in older adults. The presence of anxiety and disturbed sleep independently have been associated with greater impairment in executive functioning. However, little is known regarding the interactive effects of anxiety symptoms and poor sleep on executive functioning. The current study examined the role of sleep efficiency as a moderator of anxiety's effect on executive functioning. Methods: Baseline measures from the Active Adult Mentoring Project were used for secondary analyses. Participants included 91 community-dwelling older adults ( M age=63.51). Anxiety symptoms were measured using trait-anxiety scores from the State-Trait Anxiety Inventory. Sleep efficiency was calculated from self-reported sleep diaries completed over 7 consecutive days. Two cognitive tests were utilized to assess executive functioning: Trail Making Test-Trails B and Letter Series. Hierarchical regressions were performed to assess the association of anxiety symptoms, sleep efficiency, and the interaction between anxiety symptoms and sleep efficiency on executive functioning. All variables were mean-centered prior to analyses. Results: Neither sleep efficiency, nor anxiety symptoms were significant independent predictors of executive functioning ( p 's>.05). The anxiety symptoms-sleep efficiency interaction significantly predicted Trails B, t (79)=-2.23, p =.029, β =-.25, and Letter Series performance, t (78)=2.74, p =.01, β =.31. Models explained a significant amount of variance in executive functioning (Trails B R 2 =.16; Letter Series R 2 =.12). Specifically, individuals with high anxiety symptoms, but high sleep efficiency demonstrated better executive functioning than those with high anxiety symptoms and low sleep efficiency. Conclusion: Sleep efficiency may serve as a protective factor for individuals with higher levels of anxiety symptoms. Treating older adults with poor sleep and high anxiety may mitigate cognitive consequences. Future investigations would be well suited to incorporate anxiety symptoms into the study of the link between sleep and executive functioning. Examining the interactive effects of anxiety symptoms and sleep on other cognitive domains may be informative. Support (If Any): This work was supported by the National Institute on Aging (1R36AG029664-01, PI: Aiken-Morgan; T32AG020499, PI: Marsiske; F31AG032802, PI: Dzierzewski; 1K23AG049955, PI: Dzierzewski) and University of Florida (Age Network research award, PI: McCrae).